2020
DOI: 10.1111/petr.13728
|View full text |Cite
|
Sign up to set email alerts
|

The impact of donor full‐length KIR2DS4 in the development of acute and chronic GVHD after unrelated allogeneic HSCT

Abstract: Background Killer Ig‐like receptor 2DS4 (KIR2DS4) is the most prevalent activating killer Ig‐like receptor gene. It is divergent and encodes either full‐length or deleted allele variants. The studies of donor killer KIR2DS4 in unrelated allogeneic hematopoietic stem cell transplantations were limited. Methods KIR and HLA genotyping were determined in 75 pairs of Chinese pediatric hematologic malignancy patients. Results Among the 75 donor‐recipient pairs, 77.3% (58/75) of the donors were positive for full‐leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated that patients with KIR2DS4 positive donors had a higher incidence of graft versus host disease (GVHD) after HSCT. KIR2DS4 expression level may serve as a good predictor of GVHD occurrence after transplantation [30,31]. Studies have found that APOBEC3G had signi cant carcinogenic activity and was highly expressed in a variety of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that patients with KIR2DS4 positive donors had a higher incidence of graft versus host disease (GVHD) after HSCT. KIR2DS4 expression level may serve as a good predictor of GVHD occurrence after transplantation [30,31]. Studies have found that APOBEC3G had signi cant carcinogenic activity and was highly expressed in a variety of tumors.…”
Section: Discussionmentioning
confidence: 99%